Determination Of Strength And Deformability Of Fractured Rock Mass By Finite Elemental Modelling - Aminuddin, Emirol Amri (Universiti Sains Malaysia, 2017)
Rock deformation and strength of rock is one of the geotechnical problem that has to be taken into consideration by engineers when dealing with the design of any type of modern structures. In present work, the deformability and strength of fractured rock mass is determined by applying the Finite Elemental Method by using the software RS2. The model was applied to study the scale dependency of both strength and deformability of fractured rock mass. Also, the fracture/joint behaviour is studied by using this method. Joint analysis is carried out by using Dips 7.0 by using the Rosette plot. Joint parameters of 6 and 11 are chosen to be used in the model for Finite Elemental Analysis. The dip directions are 6.58 and 326 degrees respectively. The intact rock properties as acquired from the fieldwork was analysed first by using Rocdata before being inserted into the modelling procedure in RS2. The results show that the accepted representative elementary volume for the strength and deformability of fractured rock mass is 12 m by using the acceptable coefficient of variation of 1.5%.